ANTECEDENTS OF TRUST TOWARDS THE ATTITUDE OF CHARITABLE ORGANISATION IN MONETARY PHILANTHROPIC DONATION AMONG GENERATION-Y - Siti Hasnah Hassan; Tajul Ariffin Masron; Noor Mohamed; Ramayah Thurasamy (Asian Academy of Management Journal, 2018)
Monetary philanthropic donation, which is held through charitable organisation (CO), is known as a voluntary contribution in the form of money. The purpose of this donation is to improve public’s welfare, where there is little to no commensurate reward given to the donor. Furthermore, the organisation is fully responsible for the money used for donation. Therefore, an understanding in regards of the donor’s attitude and perception is essential for CO, in order to improve the philanthropic behaviour displayed by the public. Following that, the purpose of this research is to identify the relationship between trust disposition, perceived ability, perceived integrity, perceived benevolence, the attitude towards CO, and the influence of these factors towards young generation behaviour during monetary philanthropic donation. Pertaining to these factors, through self-administered questionnaire, a survey was conducted to collect data from 258 respondents from Generation-Y or Gen-Y in Malaysia. The data was then analysed using SmartPLS 3.2.6. Based on the findings obtained from the survey, it was shown that philanthropic monetary donation held through CO is indirectly influenced by the perceived ability and integrity displayed through the public’s attitude towards CO. Out of all factors, perceived integrity, perceived ability, and perceived benevolence were found to directly influence the attitude displayed by public towards CO. On the contrary, it was a surprising fact that there is a small relation between trust disposition and the public’s attitude towards CO. Besides, the attitude displayed towards CO does not mediate the relationship between trust disposition and philanthropic behaviour. The findings provide valuable insight to scholars, marketing practitioners, and COs in their understanding of the complex philanthropic behaviour shown by individuals.